The role of mass and environment in the quenching and structural transformation of galaxies up to z ~3 - Fernandes Ramos, Marta Sofia (2021)
It is not very well understood how galaxies quench their star formation and undergo morphological transformation. It is hard to separate how both the internal structure of galaxies and their environment affect their star formation properties. Furthermore, the observed morphological and size evolution of galaxies is still a topic of much research.